A high efficiency HPF-ZCS-PWM Sepic for electronic ballast with multiple tubular fluorescent lamps - Wakabayashi, Fabio Toshiaki [UNESP]; Canesin, Carlos Alberto [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2002)
This paper presents a high efficiency Sepic rectifier for an electronic ballast application with multiple fluorescent lamps. The proposed Sepic rectifier is based on a Zero-Current-Switching (ZCS) Pulse-Width-Modulated (PWM) soft-commutation cell. The high power-factor of this structure is obtained using the instantaneous average-current control technique, in order to attend properly IEC61000-3-2 standards. The inverting stage of this new electronic ballast is a classical Zero-Voltage-Switching (ZVS) Half-Bridge inverter. A proper design methodology is developed for this new electronic ballast, and a design example is presented for an application with five fluorescent lamps 40W-T12 (200W output power), 220Vrms input voltage, 130Vdc dc link voltage, with rectifier and inverter stages operating at 50kHz. Experimental results are also presented. The THD at input current is equal to 6.41%, for an input voltage THD equal to 2.14%, and the measured overall efficiency is about 92.8%, at rated load.
Keywords: Electric current control; Electric inverters; Electric rectifiers; Electronic equipment; Fluorescent lamps; Pulse width modulation; Switching; Electronic ballasts; Ballasts (lamp)